Distribution and density of the zacatuche rabbit (Romerolagus diazi) at the Protected Natural Area "Corredor Biológico Chichinautzin" - Areli Rizo-Aguilar (Therya, 2016)
The Protected Natural Area (PNA) “Corredor Biológico Chichinautzin” contains a large area of bunchgrasses, a habitat that is necessary for the zacatuche rabbit to survive. As part of a monitoring program used to evaluate the status of the zacatuche rabbit’s populations within this PNA, we estimated its distribution by using direct (sightings) and indirect methods (latrines) during visits performed to all the available habitats. Additionally, we estimated the annual density of the zacatuche rabbit using a line transect method, sampling eight, one-kilometer-long transects monthly during one year. Based on 101 latrine records and 48 sightings, a distribution map was prepared for the region using the convex polygon method in ArcView. Most of this distribution (166.43 km 2 ) represents an area that had not been previously reported in the literature for the zacatuche rabbit. Using the half-normal model that best fit the data, we estimated a density of 4.2 rabbits/ha. Our results suggest that the Corredor Biológico Chichinautzin meets the criteria necessary to be cataloged as a core distribution area for the zacatuche rabbit. Therefore, we suggest that both management and conservation of this habitat within the PNA should be made a priority.